2009
DOI: 10.1007/s00270-009-9715-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravascular Iodinated Contrast Media on Natural Course of End-Stage Renal Disease Progression in Hemodialysis Patients: A Prospective Study

Abstract: We evaluated the impact of intravascular iodinated contrast medium on residual diuresis in hemodialyzed patients. Two groups of clinically stable hemodialyzed patients with residual diuresis minimally 500 ml of urine per day were studied. The patients from the first group were given iso-osmolal contrast agent iodixanol (Visipaque, GE Healthcare, United Kingdom) in concentration of iodine 320 mg/ml with osmolality 290 mOsm/kg of water during the endovascular procedure. The second control group was followed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Of 1489 potentially eligible references, 19 (1.3%) ultimately proved eligible for review of the full article. Six additional studies were excluded from this analysis, because the investigators did not analyze AKI as defined by increases in SCr level (32)(33)(34)(35), they did not exclusively analyze patients who received IV contrast medium (36), or they did not exclusively examine CIN (37). The final number of included studies was 13 (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50).…”
Section: Meta-analysismentioning
confidence: 99%
“…Of 1489 potentially eligible references, 19 (1.3%) ultimately proved eligible for review of the full article. Six additional studies were excluded from this analysis, because the investigators did not analyze AKI as defined by increases in SCr level (32)(33)(34)(35), they did not exclusively analyze patients who received IV contrast medium (36), or they did not exclusively examine CIN (37). The final number of included studies was 13 (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50).…”
Section: Meta-analysismentioning
confidence: 99%
“…A recent study compared forty-two patients with ESRD on hemodialysis with urine volume > 0.6 L/day who received iodixanol to an age and urine volume-matched cohort of ESRD hemodialysis patients with no contrast exposure. At three months after contrast exposure there was a decline in urine volume in both groups with no statistically significant difference 89 . Similar findings have been noted in PD patients, where only a temporary decrease in RKF was noted after contrast exposure 90 .…”
Section: Considerations To Preserve Rkf In Hemodialysis Patientsmentioning
confidence: 73%
“…Nevertheless, most of physicians in practical field don't pay particular attention to these patients undergoing the procedure using contrast. Furthermore, Janousek, et al7 recently reported that residual renal function is not significantly influenced by intravascular administration of iso-osmolal iodinated contrast agent (iodixanol) in ESRD, and that its use in these patients is relatively safe and even more recommendable than magnetic resonance imaging with its potential risk of nephrogenic systemic fibrosis. In contrary to the above, however, we have seen that many dialysis patients experience fatigue, malaise, loss of appetite, and general prostration and they have even fear of retesting, after the procedure using iodinated contrast media such as computed tomography (CT) or angiogram.…”
Section: Introductionmentioning
confidence: 99%